Research Progress of Neutrophil-Mediated Drug Delivery Strategies for Inflammation-Related Disease - Yang Zhao; Haigang Zhang; Qixiong Zhang; Hui Tao (MDPI AG, 2023)
As the most abundant white blood cells in humans, neutrophils play a key role in acute and chronic inflammation, suggesting that these cells are a key component of targeted therapies for various inflammation-related diseases. Specific enzyme-responsive or specific ligand-modified polymer nanoparticles are beneficial for improving drug efficacy, reducing toxicity, and enhancing focal site retention. However, there remain significant challenges in biomedical applications of these synthetic polymer nanoparticles, mainly due to their rapid clearance by the reticuloendothelial system. In recent years, biomimetic drug delivery systems such as neutrophils acting directly as drug carriers or neutrophil-membrane-coated nanoparticles have received increasing attention due to the natural advantages of neutrophils. Thus, neutrophil-targeted, neutrophil-assisted, or neutrophil-coated nanoparticles exhibit a prolonged blood circulation time and improved accumulation at the site of inflammation. Despite recent advancements, further clinical research must be performed to evaluate neutrophil-based delivery systems for future biomedical application in the diagnosis and treatment of related inflammatory diseases. In this review, we have summarized new exciting developments and challenges in neutrophil-mediated drug delivery strategies for treating inflammation-related diseases.